(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article presents a comprehensive analysis of strategies for developing personal spiritual intelligence (SI) and ensuring digital spiritual security in the contemporary technological era. Spiritual intelligence, defined as the capacity to apply spiritual resources and values to enhance daily functioning and wellbeing, has emerged as a critical construct for human flourishing in increasingly complex and digitally-mediated environments. Drawing on theoretical frameworks from Zohar and Marshall, King, Amram, and Wigglesworth, alongside empirical research demonstrating the trainability and benefits of SI, this article synthesizes evidence-based strategies for SI development including contemplative practices, meaning-making interventions, transcendence cultivation, and conscious state expansion. Additionally, the article addresses the novel challenge of maintaining spiritual wellbeing in digital environments—termed "digital spiritual security"—examining threats posed by technology to spiritual development and proposing protective strategies including digital mindfulness, intentional technology use, value-aligned digital engagement, and cultivation of offline sacred spaces. The integration of SI development with digital spiritual security represents an essential framework for human flourishing in the twenty-first century.